Preparation of heterojunction photocatalyst and application of heterojunction photocatalyst in treatment of uranium-containing wastewater

By using polystyrene nanosphere support to coat TiO2 and introduce carbon quantum dots to construct the S-type heterojunction photocatalyst, the problems of low uranium extraction efficiency and photocatalyst stability in uranium ore wastewater were solved, and efficient and stable uranium photocatalytic removal was achieved.

CN119565671APending Publication Date: 2025-03-07SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411761245.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has problems such as single treatment targets, high cost and low uranium extraction efficiency when treating uranium ore wastewater, and traditional photocatalysts have problems such as low visible light response, serious electron hole recombination and lack of active sites.

Method used

Polystyrene nanospheres (PSs) were used as support to construct S-type heterojunction photocatalysts (PS-TiO2@CQDs) by coating TiO2 and introducing carbon quantum dots (CQDs) to improve photocatalytic activity and selectivity to uranium.

Benefits of technology

It has achieved efficient photocatalytic removal of uranium, with a removal rate of more than 99%, and has anti-ion interference, chemical stability and good cycling performance, solving the problems of catalyst recovery and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565671A_ABST
    Figure CN119565671A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a heterojunction photocatalyst and application of the heterojunction photocatalyst in treatment of uranium-containing wastewater. The preparation comprises the following steps: step 1, preparing polystyrene nanospheres; step 2, preparing PS-TiO2 (Polystyrene); and 3, adding PS-TiO2 prepared in the step 2 into ethanol, carrying out ultrasonic dispersion, adding a carbon quantum dot solution, carrying out a stirring reaction at a certain temperature for a certain time, carrying out centrifugation, washing with ethanol and deionized water to obtain a faint yellow product, and drying the faint yellow product to obtain the heterojunction photocatalyst. The heterojunction photocatalyst PS-TiO2-coated CQDs is synthesized by taking a support type material polystyrene nanosphere as a substrate, coating the surface of the substrate with a photocatalyst TiO2 and introducing carbon quantum dots to construct an S-type heterojunction coupling in-situ surface active site modification strategy, and the heterojunction photocatalyst PS-TiO2-coated CQDs shows extremely high photocatalytic activity and special selectivity to uranium, and can be applied to the field of uranium treatment. The PS-TiO2-coated CQDs show excellent ion interference resistance, chemical stability and cycle performance in a uranium-containing solution, and the photocatalytic removal rate of the PS-TiO2-coated CQDs to U (VI) is greater than 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of radioactive element treatment, and more specifically, relates to the preparation of a heterojunction photocatalyst and its application in treating uranium-containing wastewater. Background Art

[0002] The sustainable development of nuclear energy is a difficult problem that all countries have to face at present. Uranium is the main element for producing nuclear energy. Due to its easy migration characteristics, uranium is contained in a large amount of uranium in the waste liquid. If it is not discharged without treatment, it will cause great harm to the environment and people's health. Uranium mining is the first step in the nuclear fuel cycle, and it mainly produces uranium mine wastewater with rich metal cations, high concentration and complex environment. The current wastewater treatment technology has problems such as single treatment target and high cost. In addition, the metal cations in the wastewater will compete with U(VI) for active sites, resulting in low uranium extraction efficiency. Photocatalytic technology, as a green and efficient technology that has natural selectivity for non-valence ions, can well avoid the interference of metal cations and achieve efficient separation of U(VI) in complex environments. In 1967, Professor Akira Fujishima first discovered the photocatalytic performance of TiO2, and then researchers conducted extensive research on TiO2. Due to the problems of low visible light response, serious electron-hole pair recombination, and lack of active sites of TiO2 itself, the application of photocatalytic reduction of U(VI) has been limited. Although there are many ways to modify photocatalysts, including element doping, surface defects, and heterojunction construction, it is difficult to simultaneously meet the requirements of strong visible light response, efficient separation of electrons and holes, and construction of active sites. Therefore, exploring photocatalysts that have both a suitable band gap structure and abundant active sites is of great significance for the enrichment and separation of uranium from uranium mine wastewater.

[0003] In addition, there is a crucial problem in the application of photocatalysts. Most of the current photocatalysts are powder materials, which need to be in full contact with U(VI) during the treatment process. This requires the catalyst to have good hydrophilicity, which makes it very difficult to separate the catalyst from the treatment liquid. The catalyst may also cause secondary pollution. For this reason, supported catalysts have attracted widespread attention from scientific researchers. In order to meet the actual needs of industrial applications, it is very important to develop highly stable, low-cost, green and non-toxic supported photocatalysts. Polystyrene nanospheres (PSs) are an environmentally friendly material with good conductivity, strong stability, and rich functional groups on the surface. Due to their low density, they can float on the water surface, which is conducive to the absorption of natural light. These unique advantages make PSs a good catalyst support for the photocatalytic reduction of uranium in uranium mine wastewater. Summary of the invention

[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0005] In order to achieve these purposes and other advantages of the present invention, a method for preparing a heterojunction photocatalyst is provided, comprising the following steps:

[0006] Step 1, preparing polystyrene nanospheres;

[0007] Step 2, preparing PS-TiO2;

[0008] Step 3: Add the PS-TiO2 prepared in step 2 to ethanol, ultrasonically disperse it, then add the carbon quantum dot solution, stir and react at a certain temperature for a certain time, then centrifuge, wash with ethanol and deionized water to obtain a light yellow product, and dry it to obtain the heterojunction photocatalyst PS-TiO2@CQDs.

[0009] Preferably, in the step 1, the specific method for preparing polystyrene nanospheres is: mixing ammonium persulfate and polyvinyl pyrrolidone, then adding ethanol and deionized water, stirring at room temperature for 5 to 20 minutes, then adding styrene, heating the oil bath to 60 to 80° C., stirring and reacting for 5 to 7 hours, and after the reaction is completed, placing in ice water, standing for 20 to 40 minutes, then centrifuging, rinsing with deionized water, and vacuum drying at 50 to 70° C. for 10 to 16 hours to obtain polystyrene nanospheres.

[0010] Preferably, the mass volume ratio of the ammonium persulfate, polyvinyl pyrrolidone, ethanol, deionized water and styrene is 10-30 mg: 5-15 mg: 20-30 mL: 1-5 mL: 2-2.5 mL.

[0011] Preferably, in step 2, the specific method for preparing PS-TiO2 is:

[0012] S21, dispersing the polystyrene nanospheres prepared in step 1 in ethanol, stirring for 20 to 40 minutes, adding hexadecylamine and ammonia water, and continuing to stir to form a uniform suspension, then adding isopropyl titanate, stirring for 0.5 to 1.5 hours, centrifuging, and washing alternately with ethanol and deionized water, and vacuum drying at 60° C. for 10 to 16 hours to obtain a PS-TiO2 precursor;

[0013] S22. Add the PS-TiO2 precursor to a mixed solution of ethanol and deionized water, ultrasonicate for 20 to 40 minutes, then complete the crystallization process through a hydrothermal reaction, wash with ethanol and deionized water, and vacuum dry at 60°C for 10 to 16 hours to obtain PS-TiO2.

[0014] Preferably, in S21, the mass volume ratio of polystyrene nanospheres, ethanol, hexadecylamine, ammonia water and isopropyl titanate is 500-600 mg: 100-150 mL: 1-2 g: 2-6 mL: 0.5-2 mL.

[0015] Preferably, in S22, the mass volume ratio of PS-TiO2 precursor, ethanol and deionized water is 0.02-0.1 g:10-30 mL:30-70 mL; the temperature of the hydrothermal reaction is 150-170°C, and the time is 10-14 hours.

[0016] Preferably, in step three, the concentration of the carbon quantum dot solution is 0.5-2 mg / mL.

[0017] Preferably, the mass volume ratio of the PS-TiO2, ethanol and carbon quantum dot solution is 0.05-0.2 g:10-30 mL:0.1-0.5 mL.

[0018] Preferably, in the step three, the ultrasonic dispersion is performed for 5 to 20 minutes, the reaction temperature is 60 to 80° C., and the reaction time is 10 to 14 hours.

[0019] Preferably, in the step three, before using PS-TiO2, the PS-TiO2 is pretreated: the PS-TiO2 is placed in ethanol, ultrasonically dispersed for 10 to 20 minutes, hydrazine hydrate and titanate coupling agent are added, and stirred in an oil bath at 60 to 80° C. for 4 to 8 hours, the precipitate is collected by centrifugal filtration, and washed alternately with ethanol and deionized water, and vacuum dried to obtain pretreated PS-TiO2.

[0020] Preferably, the mass volume ratio of PS-TiO2 and ethanol is 1 g:50-200 mL, and the mass ratio of PS-TiO2, hydrazine hydrate and titanate coupling agent is 1:0.05-0.3:0.1-0.5.

[0021] Preferably, the titanate coupling agent is one or both of isopropyl tri(dioctyl pyrophosphate acyloxy) titanate and isopropyl dioleyloxy(dioctyl phosphate acyloxy) titanate.

[0022] Application of a heterojunction photocatalyst prepared by the preparation method as described above in treating uranium-containing wastewater.

[0023] The present invention at least includes the following beneficial effects: the present invention uses a supporting material polystyrene nanosphere (PSs) as a substrate, coats a photocatalyst (TiO2) on its surface, and constructs an S-type heterojunction coupled with an in-situ surface active site modification strategy by introducing carbon quantum dots (CQDs) to synthesize a heterojunction photocatalyst (PS-TiO2@CQDs), which exhibits extremely strong photocatalytic activity and special selectivity for uranium. PS-TiO2@CQDs exhibits excellent resistance to ion interference, chemical stability and cycle performance in uranium-containing solutions, and the photocatalytic removal rate of U(VI) is greater than 99%; the present invention utilizes the floatability of PSs, which can not only increase the absorption of natural light, but also enhance the recyclability of the material, thereby solving the problem that traditional catalysts are difficult to recycle; the present invention solves the problem of catalyst defects itself by constructing an S-type heterojunction, enhances the electron-hole separation ability, and retains a stronger redox ability, which is beneficial to the efficient reduction of U(VI); the present invention provides a new direction for the development of advanced photocatalysts with efficient charge separation that meet industrial needs, and provides a new idea and new material for the photocatalytic treatment technology of uranium mine wastewater.

[0024] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 a is a physical picture of the performance of PS-TiO2@CQDs and TiO2 prepared in Example 1 in aqueous solution; Figure 1 b is the physical picture of TiO2 and PS-TiO2@CQDs after filtration;

[0026] Figure 2 a is the SEM image of PSs prepared in Comparative Example 1; Figure 2 b is the SEM image of PS-TiO2 prepared in Comparative Example 2; Figure 2 c is the TEM image of PS-TiO2@CQDs prepared in Example 1; Figure 2 d is the TEM-EDX element mapping image of PS-TiO2@CQDs prepared in Example 1; Figure 2 e is the XRD spectrum of PS-TiO2 prepared in Comparative Example 2 and PS-TiO2@CQDs prepared in Example 1; Figure 2 f is the HRTEM image of PS-TiO2@CQDs prepared in Example 1;

[0027] Figure 3 a is the XPS total spectra of PSs prepared in Comparative Example 1, PS-TiO2 prepared in Comparative Example 2, and PS-TiO2@CQDs prepared in Example 1; Figure 3b is the C1sXPS spectra of PS-TiO2 and PS-TiO2@CQDs; Figure 3 c is the O1sXPS spectra of PSs and PS-TiO2@CQDs; Figure 3 d is the XPS spectra of Ti 2p of PS-TiO2 and PS-TiO2@CQDs;

[0028] Figure 4 a is a schematic diagram of the energy band structure of CQDs and PS-TiO2; Figure 4 b is the electron transfer model of PS-TiO2@CQDs S-type heterojunction;

[0029] Figure 5 a is the time curve of the dark reaction of PS-TiO2@CQDs-X prepared in Examples 1 to 4 to remove U(VI); Figure 5 b is the time curve of the removal of U(VI) by PS-TiO2@CQDs-X-ray reaction prepared in Examples 1 to 4;

[0030] Figure 6 The time curves of the photocatalytic reduction of U(VI) by PSs prepared in Comparative Example 1, PS-TiO2 prepared in Comparative Example 2, and PS-TiO2@CQDs prepared in Example 1;

[0031] Figure 7 a is the removal rate of U(VI) by PS-TiO2@CQDs prepared in Example 1 under the influence of different interfering ions; Figure 7 b is the removal rate of U(VI) by PS-TiO2@CQDs prepared in Example 1 under different pH conditions; Figure 7 c is the removal rate of U(VI) by PS-TiO2@CQDs prepared in Example 1 at different initial concentrations of U(VI); Figure 7 d is the removal rate of U(VI) by PS-TiO2@CQDs prepared in Example 1 after 6 cycles;

[0032] Figure 8 a is the removal rate of U(VI) by the heterojunction photocatalyst prepared in Example 5 after 6 cycles; Figure 8 b is the removal rate of U(VI) by the heterojunction photocatalyst prepared in Example 6 after 6 cycles;

[0033] Fig. 9 a is the U 4f XPS spectrum of the PS-TiO2@CQDs prepared in Example 1 after dark reaction and light reaction; Fig. 9 b is the XRD spectrum of PS-TiO2@CQDs prepared in Example 1 before and after the photocatalytic reaction;

[0034] Fig.10a is the O2 before and after illumination in the U(VI) photocatalytic reduction test - and OH - ESR signal; Fig.10 b is the scavenger test result of PS-TiO2@CQDs prepared in Example 1. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0036] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0037] Example 1

[0038] A method for preparing a heterojunction photocatalyst comprises the following steps:

[0039] Step 1, weigh 20 mg of ammonium persulfate (APS) and 0.01 g of polyvinyl pyrrolidone (PVP) and put them into a vial, then add 25 mL of ethanol and 3 mL of deionized water, stir at room temperature for 10 minutes, then add 2.2 mL of styrene, put the vial into an oil bath, control the temperature at 70 ° C, and stir well for 6 hours to complete the polymerization reaction, then put the vial into ice water, let it stand for 30 minutes to terminate the reaction, then centrifuge, repeatedly rinse the precipitate with deionized water, and place it in a vacuum drying oven at 60 ° C for 12 hours to obtain polystyrene nanospheres (PSs);

[0040] Step 2: Weigh 550 mg of PSs and disperse it in 125 mL of ethanol. After stirring for 30 minutes, add 1.6 g of hexadecylamine (HDA) and 4 mL of ammonia water (NH3·H2O), continue stirring to form a uniform suspension, and then quickly add 1 mL of isopropyl titanate to avoid hydrolysis in the air. After stirring for 1 hour, centrifuge, and wash the precipitate alternately with ethanol and deionized water several times, and place it in a vacuum drying oven at 60°C for 12 hours to obtain a PS-TiO2 precursor.

[0041] Step 3, weigh 0.1g of PS-TiO2 precursor and put it into a mixed solution of 40mL of ethanol and 100mL of deionized water, ultrasonicate for 30 minutes, then transfer the mixture into a polytetrafluoroethylene liner, complete the crystallization process by hydrothermal method, keep it at 160°C for 12 hours, wash it with ethanol and deionized water, and dry it in a vacuum oven at 60°C for 12 hours to obtain PS-TiO2;

[0042] Step 4: Weigh 0.1 g of PS-TiO2, put it into a vial, add 20 mL of ethanol to the vial, ultrasonically disperse it for 10 minutes, then add 0.2 mL of carbon quantum dot solution (1 mg / mL), and put it into an oil bath and stir and heat it to 70°C. After stirring and reacting for 12 hours, the product was centrifuged and washed with ethanol and deionized water to obtain a light yellow product. After drying, a heterojunction photocatalyst (PS-TiO2@CQDs) was obtained, which was recorded as PS-TiO2@CQDs-2.

[0043] Example 2

[0044] In this embodiment, the amount of carbon quantum dot solution used is 0.3 mL, and the remaining steps are the same as in Example 1 to obtain a heterojunction photocatalyst, which is recorded as PS-TiO2@CQDs-3.

[0045] Example 3

[0046] In this embodiment, the amount of carbon quantum dot solution used is 0.4 mL, and the remaining steps are the same as in Example 1 to obtain a heterojunction photocatalyst, which is recorded as PS-TiO2@CQDs-4.

[0047] Example 4

[0048] In this embodiment, the amount of carbon quantum dot solution used is 0.5 mL, and the remaining steps are the same as in Example 1 to obtain a heterojunction photocatalyst, which is recorded as PS-TiO2@CQDs-5.

[0049] Example 5

[0050] Before using PS-TiO2 in step 4, PS-TiO2 is pretreated: PS-TiO2 is placed in ethanol, ultrasonically dispersed for 10 minutes, hydrazine hydrate and titanate coupling agent NDZ-201 (isopropyl tri(dioctyl pyrophosphate) titanate) are added, and stirred in an oil bath at 70°C for 5 hours. The precipitate is collected by centrifugal filtration, and washed alternately with ethanol and deionized water, and vacuum dried at 60°C for 12 hours to obtain pretreated PS-TiO2; wherein the mass volume ratio of PS-TiO2 and ethanol is 1 g:100 mL, and the mass ratio of PS-TiO2, hydrazine hydrate and titanate coupling agent is 1:0.1:0.3; the remaining steps are the same as in Example 1 to obtain a heterojunction photocatalyst, recorded as PS-TiO2@CQDs-2-1.

[0051] In this embodiment, PS-TiO2 is pretreated by adding hydrazine hydrate and titanate coupling agent to improve its dispersibility and binding properties. The treated PS-TiO2 is better combined with carbon quantum dots, and the obtained PS-TiO2@CQDs is more stable. At the same time, it can also increase active sites, introduce nitrogen elements, and improve the photocatalytic performance of the material. Its U(VI) removal rate and cycle stability are further improved.

[0052] Example 6

[0053] Before using PS-TiO2 in step 4, the PS-TiO2 is pretreated: put PS-TiO2 into ethanol, ultrasonically disperse it for 10 minutes, then add hydrazine hydrate, stir it in an oil bath at 70°C for 5 hours, collect the precipitate by centrifugal filtration, and wash it alternately with ethanol and deionized water, and vacuum dry it at 60°C for 12 hours to obtain pretreated PS-TiO2; wherein the mass volume ratio of PS-TiO2 to ethanol is 1g:100mL, and the mass ratio of PS-TiO2 to hydrazine hydrate is 1:0.1; the remaining steps are the same as in Example 1 to obtain a heterojunction photocatalyst, recorded as PS-TiO2@CQDs-2-2.

[0054] Comparative Example 1

[0055] Preparation method of polystyrene nanospheres (PSs):

[0056] Weigh 20 mg of ammonium persulfate and 0.01 g of polyvinyl pyrrolidone into a vial, then add 25 mL of ethanol and 3 mL of deionized water, stir at room temperature for 10 minutes, then add 2.2 mL of styrene, put the vial into an oil bath, control the temperature at 70°C, and stir well for 6 hours to complete the polymerization reaction, then put the vial into ice water, let it stand for 30 minutes to terminate the reaction, then centrifuge, repeatedly rinse with deionized water, and put it into a vacuum drying oven at 60°C for 12 hours to obtain polystyrene nanospheres (PSs).

[0057] Comparative Example 2

[0058] Preparation method of PS-TiO2:

[0059] Step 1, weigh 20 mg of ammonium persulfate and 0.01 g of polyvinyl pyrrolidone and put them into a vial, then add 25 mL of ethanol and 3 mL of deionized water, stir at room temperature for 10 minutes, then add 2.2 mL of styrene, put the vial into an oil bath, control the temperature at 70 ° C, and stir well for 6 hours to complete the polymerization reaction, then put the vial into ice water, let it stand for 30 minutes to terminate the reaction, then centrifuge, repeatedly rinse with deionized water, put it into a vacuum drying oven at 60 ° C for 12 hours to obtain polystyrene nanospheres (PSs);

[0060] Step 2: Weigh 550 mg of PSs and disperse it in 125 mL of ethanol. After stirring for 30 minutes, add 1.6 g of hexadecylamine and 4 mL of ammonia water. Continue stirring to form a uniform suspension. Then quickly add 1 mL of isopropyl titanate to avoid hydrolysis in the air. After stirring for 1 hour, centrifuge and wash alternately with ethanol and deionized water for several times. Place in a vacuum drying oven at 60 ° C for 12 hours to obtain a PS-TiO2 precursor.

[0061] Step 3: Weigh 0.05 g of PS-TiO2 precursor and put it into a mixed solution of 20 mL of ethanol and 50 mL of deionized water. Ultrasonicate for 30 minutes, then transfer the mixture into a polytetrafluoroethylene liner and complete the crystallization process by hydrothermal method. Keep it at 160°C for 12 hours, wash it with ethanol and deionized water, and place it in a vacuum drying oven at 60°C for 12 hours to obtain PS-TiO2.

[0062] Unless otherwise specified, the PS-TiO2@CQDs used in subsequent experiments are PS-TiO2@CQDs-2 prepared in Example 1.

[0063] The present invention synthesizes PSs and PS-TiO2 by template method and hydrothermal method, and then loads CQDs onto the surface of PS-TiO2 by electrostatic self-assembly to obtain PS-TiO2@CQDs; Figure 1 As shown in a, the traditional powdered TiO2 and PS-TiO2@CQDs are placed in aqueous solution respectively. It can be clearly seen that the powdered TiO2 sinks to the bottom of the bottle, while the PS-TiO2@CQDs float on the water surface, and there is no turbidity at the bottom of the bottle; due to the floating property of PS-TiO2@CQDs, the catalyst can be recovered by simple filtration, such as Figure 1 As shown in Figure b, after simple filtration, the filtered product needs to be dried due to the hydrophilicity of powdered TiO2. However, after filtering PS-TiO2@CQDs, solid-liquid separated PS-TiO2@CQDs can be directly obtained without drying. This is caused by the abundant hydrophobic groups on the surface of PSs. Based on this phenomenon, the successful synthesis of the floating photocatalyst is preliminarily proved. Figure 2 ac are the SEM images of PSs and PS-TiO2 and the TEM images of PS-TiO2@CQDs, respectively. Figure 2 a It can be seen that the surface of pure PSs is very smooth, with a particle size of about 800nm, while the surface of PS-TiO2 and PS-TiO2@CQDs coated with TiO2 is rough and uneven, which preliminarily verifies the successful loading of TiO2. In addition, EDS test ( Figure 2 d), it can be clearly seen that Ti and O elements are concentrated at the edge of PSs, while C elements are concentrated in the middle of PSs, which further verifies the successful loading of TiO2. Figure 2 e), we further confirmed that the substance coated on the PSs surface is TiO2. In addition, we calculated the lattice spacing and obtained Figure 2The spacing of the obvious lattice fringes in f is d = 0.341nm, which belongs to anatase. Although CQDs also have lattice fringes, due to the very good crystallinity of TiO2 and the very small scale of CQDs, about 2.5nm, the crystal form of CQDs is covered and cannot be clearly observed. Therefore, we further characterized the material by XPS.

[0064] Figure 3 a is the XPS total spectrum of PSs, PS-TiO2, and PS-TiO2@CQDs, where the signal peaks of C1s, Ti 2p, and O1s can be clearly seen. In order to further prove the successful loading of CQDs, the C1s spectrum was peak-fitted, as shown in Figure 2. Figure 3 As shown in b, the C1s spectra of PS-TiO2 and PS-TiO2@CQDs are compared. Compared with PS-TiO2, the C1s spectrum of PS-TiO2@CQDs has a new peak at 286.8±0.1eV, which is the carbon quantum dots. In addition, from the O1s spectrum ( Figure 3 c) It can be seen that there are abundant hydroxyl groups on the PSs surface (532.0±0.1eV), and there are also hydroxyl groups in the O1s spectrum of PS-TiO2@CQDs. The peak at 529.8±0.1eV belongs to lattice oxygen (Ti-O bond). The peaks at 458.6±0.1eV and 464.4±0.1eV in the Ti 2p XPS spectrum are attributed to Ti 2p 3 / 2 and Ti 2p 1 / 2 peak( Figure 3 d), the peak position of Ti 2p did not shift after the introduction of CQDs, indicating that the introduction of CQDs does not affect the lattice of TiO2.

[0065] Based on the UV-vis test results and the valence band edge test results, we drew the band structure diagrams of PS-TiO2 and CQDs, such as Figure 4 As shown in a, according to the XPS valence band edge test results, we can directly deduce that the valence band positions of PS-TiO2 and CQDs are 1.85eV and 1.35eV, respectively. According to the UV-vis test results, we can directly obtain the band gap values ​​of PS-TiO2 and CQDs, which are 2.43eV and 2.07eV, respectively. By calculating the formula CB = VB-E g, we obtained the conduction band positions of PS-TiO2 and CQDs, which are -0.58eV and -0.72eV, respectively. In addition, due to the difference in band structure, there are also differences in the Fermi level. When the two substances are in contact, the Fermi level will tend to balance, which leads to the directional migration of electrons. The electrons produced by the substance with a lower Fermi level will migrate to a place with a higher Fermi level. The Fermi level of PS-TiO2 is lower than that of CQDs. Therefore, we can confirm that the electrons migrate from PS-TiO2 to CQDs. When excited by light, a built-in electric field is formed due to the accumulation of electrons and holes, and the built-in electric field can promote the recombination of electrons and holes at the heterojunction interface. In addition, the electrons in the conduction band of PS-TiO2 and the holes in the valence band of CQDs recombine at the heterojunction interface, which enables the catalyst to maintain a stronger redox ability, which is more conducive to the efficient reduction of U(VI) under light-assisted conditions. Based on the above analysis, we successfully constructed an S-type heterojunction PS-TiO2@CQDs with high catalytic activity and effective separation of electron-hole pairs, and drew a model of the S-type electron transfer path as shown in Figure 4 As shown in b.

[0066] U(VI) photocatalytic reduction test: 5 mg photocatalyst and 20 mL U(VI) solution (C U(VI) =80 mg / L) and pH value was 5.0; in the experiments with different U(VI) concentrations, C U(VI) =10mg / L, 20mg / L, 40mg / L, 60mg / L, 80mg / L, 100mg / L; the solid-liquid ratio of the photocatalyst to the U(VI) solution in the cycle test was 1:4; in the ion interference test, an 80mg / LU(VI) solution with 80mg / L interfering ions was used, C U(VI) :C M =1:1, interfering ion M=K + , Na + , Ca 2+ , Sr. 2+ , Zn 2+ , Ba 2+ ; In the different pH tests, HNO3 and NaOH were used to change the pH value of the uranium solution (4-10); For the photocatalytic experiments, the simulated light source was a 300 W xenon lamp with an AM 1.5G filter (BL-GHX V, China), using a full spectrum wavelength and an intensity of 200 mW / cm 2The reaction system was irradiated with a xenon lamp for 120 minutes. Samples were collected at 10, 20, 30, 60, 90 and 120 minutes of illumination. The same operation was performed in a dark environment as a comparison. After the photocatalytic reaction, UO2 was measured by an ultraviolet spectrophotometer at a wavelength of 651.8 nm. 2+ The removal rate of U(VI) was calculated by the following equation:

[0067] U(VI) removal rate = (C0-C t ) / C0×100%

[0068] Where C0 is the initial concentration of U(VI), C t It is the concentration of U(VI) after a certain period of reaction.

[0069] Figure 5 a is the removal rate of U(VI) by PS-TiO2@CQDs-X prepared in Examples 1 to 4 under dark conditions, Figure 5 b is the removal rate of U(VI) by PS-TiO2@CQDs-X prepared in Examples 1 to 4 under illumination conditions. It can be seen that the photocatalytic efficiency of PS-TiO2@CQDs-2 prepared in Example 1 is the best, with a U(VI) removal rate of 99% and the fastest reaction rate, indicating that the introduction of too many CQDs will hinder the catalytic activity of the catalyst.

[0070] The catalytic performance of PSs, PS-TiO2 and PS-TiO2@CQDs in photocatalytic reduction of U(VI) was tested. Figure 6As shown in the figure, in the full dark reaction process (-120min~0min), the removal rates of U(VI) by PSs and PS-TiO2 were 10% and 7%, respectively. Due to the abundant hydroxyl groups on the surface of PSs, its removal effect on U(VI) is slightly higher than that of PS-TiO2, and this is also because most of the active sites are covered after TiO2 coating. In the light reaction, due to the photocatalytic activity of TiO2, the removal effect of U(VI) by PS-TiO2 exceeds that of PSs, reaching 15%. This also proves that PSs does not have photocatalytic activity, and its ability to remove U(VI) comes from the adsorption of U(VI) by its surface hydroxyl groups. PS-TiO2@CQDs with CQDs showed an adsorption capacity far exceeding that of PSs and PS-TiO2 at the beginning of the dark reaction, which may be caused by the synergistic effect of surface hydroxyl groups and CQDs. After sufficient dark reaction, the removal rate of U(VI) by PS-TiO2@CQDs was 47%, and the increase in the removal effect of U(VI) was very small in the first 10 minutes of the light reaction. After 30 minutes of the light reaction, the removal effect and rate of U(VI) increased rapidly. This may be because CQDs have the characteristics of photoluminescence. When CQDs receive light energy, they will not release it immediately, but store the light energy. After a certain energy saturation, they will release energy again to assist the catalyst in removing U(VI), and the final removal rate reached an astonishing 99.3%. The above results verify the synergistic effect of the integration of S-type heterojunction and surface hydroxyl modification, which promotes efficient photoelectron transfer and provides abundant active sites, thereby accelerating the reaction kinetics of U(VI).

[0071] The reduction performance and stability of PS-TiO2@CQDs to U(VI) in extreme environments were tested. First, the anti-ion interference of PS-TiO2@CQDs was verified to be strong in uranium mine wastewater. Figure 7 As shown in a, under the interference of various metal cations, the removal rate of U(VI) by PS-TiO2@CQDs can be maintained above 85%. In view of the extreme environment in uranium mine wastewater, the removal capacity of U(VI) by PS-TiO2@CQDs under different pH conditions is studied. In a wide pH range (pH = 4 to 10), PS-TiO2@CQDs exhibits excellent photocatalytic performance, and the removal rate of U(VI) can be maintained above 95% ( Figure 7 b). Through the above two experiments, it can be seen that PS-TiO2@CQDs has excellent anti-ion interference performance and chemical stability. The removal ability of PS-TiO2@CQDs in solutions with different initial U(VI) concentrations was tested. Figure 7As shown in c, in solutions with different initial U(VI) concentrations, PS-TiO2@CQDs can still maintain a removal rate of more than 95%; the cyclic stability of PS-TiO2@CQDs was tested, as shown in Figure 7 As shown in Figure d, the first U(VI) removal rate was 99.1%. After 5 cycles, the removal effect of PS-TiO2@CQDs on U(VI) was still able to maintain a very high level (removal rate>95%). The above results verify that PS-TiO2@CQDs can be used for efficient photocatalytic reduction of uranium in complex uranium mine wastewater environments.

[0072] Figure 8 a is the removal rate of U(VI) after 6 cycles of the heterojunction photocatalyst prepared in Example 5; Figure 8 b is the removal rate of U(VI) after 6 cycles of the heterojunction photocatalyst prepared in Example 6. It can be seen that the first U(VI) removal rate of the heterojunction photocatalyst prepared in Example 5 reached 99.8%, and after 5 cycles, its removal rate of U(VI) was >97%; the first U(VI) removal rate of the heterojunction photocatalyst prepared in Example 6 reached 99.5%, and after 5 cycles, its removal rate of U(VI) was >96%; the U(VI) removal rate and cycle stability of the heterojunction photocatalysts prepared in Examples 5 to 6 of the present invention are higher than those in Example 1, among which Example 5 is the highest. By adding hydrazine hydrate and titanate coupling agent to pretreat PS-TiO2, its dispersibility and binding property can be improved, so that it can be better combined with carbon quantum dots, and the obtained PS-TiO2@CQDs are more stable. At the same time, it can also increase active sites, introduce nitrogen elements, improve the photocatalytic performance of the material, and further improve its U(VI) removal rate and cycle stability.

[0073] In order to further reveal the reaction mechanism of PS-TiO2@CQDs photocatalytic removal of U(VI), XPS and XRD characterization were carried out on PS-TiO2@CQDs after U(VI) photocatalytic reduction test. Fig. 9 a is the U 4f XPS test result before and after the photoreaction. Two characteristic peaks appeared in the product of the adsorption process before the photoreaction, located at 392.4±0.1eV and 381.6±0.1eV, representing hexavalent uranium, indicating that uranium is mainly adsorbed on the catalyst surface in hexavalent form. After the photoreaction, two new peaks can be seen, located at 391.6±0.1 and 380.8±0.1eV, corresponding to tetravalent uranium. It can be seen that hexavalent uranium is first adsorbed by hydroxyl groups and then directly reduced. However, the characteristic peaks of hexavalent uranium still exist in the XPS spectrum after the photoreaction. Therefore, we also performed XRD characterization on the product after the photoreaction, as shown in the figure. Fig. 9As shown in Figure b, the reaction product detected is not UO2, but exists in the form of (UO2)O2·H2O, which indicates that in the photoreaction process, there are some intermediate products with oxidative properties, which may be oxidative free radicals. In order to further explore the cause of the generation of (UO2)O2·H2O, we conducted an ESR signal test.

[0074] like Fig.10 As shown in a, ·OH was detected during the photoreaction process. - and O2 - In order to further explore the ·OH - and O2 - To investigate the effect of U(VI) on the final product, we conducted scavenger experiments, such as Fig.10 As shown in b, silver nitrate, p-benzoquinone, tert-butyl alcohol and methanol are added to the reaction solution to specifically remove the e generated during the reaction. - 、O2 - , OH - and h + Compared with the sample without scavenger, the removal capacity of U(VI) in the sample with methanol slightly increased. This is because the addition of methanol is equivalent to the addition of sacrificial agent, which can inhibit the recombination of electron-hole pairs and enhance the electron lifetime, thereby promoting the reaction. In the sample with silver nitrate and p-benzoquinone, the removal rate dropped significantly, which further proves that e - 、O2 - It plays a major role in the reaction. The introduction of tert-butyl alcohol can eliminate ·OH - At the same time, it will cover the hydroxyl active sites on the catalyst surface, resulting in a significant decrease in the removal rate.

[0075] Based on the above results, we have summarized the reaction mechanism of PS-TiO2@CQDs photocatalytic reduction of uranium and listed the reaction equation. When PS-TiO2@CQDs are excited by light (Eq 1), part of the electrons generated are directly reduced with U(VI) through Eq 2, and the other part of the electrons are combined with O2 to generate ·O2 through Eq 3. - ,h + Combines with water to generate OH by the method of Eq 4 - . Final · O2 - and OH - Under the synergistic effect of , U(IV) on the surface of PS-TiO2@CQDs was oxidized to (UO2)O2·2H2O via Eq 5.

[0076] PS-TiO2@CQDs+hv→h + +e -(Eq 1)

[0077] U(VI)+e - →U(IV) (Eq 2)

[0078] e - +O2 → ·O2 - (Eq 3)

[0079] h + +H2O→·OH - +h + (Eq 4)

[0080] U(IV)+·OH - +·O2 - →(UO2)O2·2H2O (Eq 5)

[0081] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a heterojunction photocatalyst, characterized in that: The following steps are involved: Step 1, preparing polystyrene nanospheres; Step 2, preparing PS-TiO2; Step 3: Add the PS-TiO2 prepared in step 2 to ethanol, disperse it ultrasonically, then add the carbon quantum dot solution, stir and react at a certain temperature for a certain time, then centrifuge, wash with ethanol and deionized water to obtain a light yellow product, and dry it to obtain a heterojunction photocatalyst.

2. The method for preparing a heterojunction photocatalyst according to claim 1, characterized in that: In the step 1, the specific method for preparing polystyrene nanospheres is: ammonium persulfate and polyvinyl pyrrolidone are mixed, and then ethanol and deionized water are added, stirred at room temperature for 5 to 20 minutes, and then styrene is added, and the oil bath is heated to 60 to 80° C., and the reaction is stirred for 5 to 7 hours. After the reaction is completed, the mixture is placed in ice water, allowed to stand for 20 to 40 minutes, and then centrifuged, rinsed with deionized water, and vacuum dried at 50 to 70° C. for 10 to 16 hours to obtain polystyrene nanospheres.

3. The method for preparing a heterojunction photocatalyst according to claim 2, characterized in that: The mass volume ratio of the ammonium persulfate, polyvinyl pyrrolidone, ethanol, deionized water and styrene is 10-30 mg: 5-15 mg: 20-30 mL: 1-5 mL: 2-2.5 mL.

4. The method for preparing a heterojunction photocatalyst according to claim 1, characterized in that: In the step 2, the specific method for preparing PS-TiO2 is: S21, dispersing the polystyrene nanospheres prepared in step 1 in ethanol, stirring for 20 to 40 minutes, adding hexadecylamine and ammonia water, and continuing to stir to form a uniform suspension, then adding isopropyl titanate, stirring for 0.5 to 1.5 hours, centrifuging, and washing alternately with ethanol and deionized water, and vacuum drying at 60° C. for 10 to 16 hours to obtain a PS-TiO2 precursor; S22. Add the PS-TiO2 precursor to a mixed solution of ethanol and deionized water, ultrasonicate for 20 to 40 minutes, then complete the crystallization process through a hydrothermal reaction, wash with ethanol and deionized water, and vacuum dry at 60°C for 10 to 16 hours to obtain PS-TiO2.

5. The method for preparing a heterojunction photocatalyst according to claim 4, characterized in that: In the S21, the mass volume ratio of the polystyrene nanospheres, ethanol, hexadecylamine, ammonia water and isopropyl titanate is 500-600 mg: 100-150 mL: 1-2 g: 2-6 mL: 0.5-2 mL.

6. The method for preparing a heterojunction photocatalyst according to claim 4, characterized in that: In the S22, the mass volume ratio of the PS-TiO2 precursor, ethanol and deionized water is 0.02-0.1 g:10-30 mL:30-70 mL; the temperature of the hydrothermal reaction is 150-170° C., and the time is 10-14 hours.

7. The method for preparing a heterojunction photocatalyst according to claim 1, characterized in that: In the step 3, the concentration of the carbon quantum dot solution is 0.5-2 mg / mL.

8. The method for preparing a heterojunction photocatalyst according to claim 7, characterized in that: The mass volume ratio of the PS-TiO2, ethanol and carbon quantum dot solution is 0.05-0.2 g:10-30 mL:0.1-0.5 mL.

9. The method for preparing a heterojunction photocatalyst according to claim 1, characterized in that: In the step 3, ultrasonic dispersion is performed for 5 to 20 minutes, the reaction temperature is 60 to 80° C., and the reaction time is 10 to 14 hours.

10. Use of a heterojunction photocatalyst prepared by the preparation method according to any one of claims 1 to 9 in treating uranium-containing wastewater.